Review of chemical looping process for carbonaceous feedstock Conversion: Rational design of oxygen carriers. (1st October 2022) - Zhang, Xiaorong; Zhang, Fusen; Song, Zhanlong; Lin, Leteng; Zhao, Xiqiang; Sun, Jing; Mao, Yanpeng; Wang, Wenlong
Highlights: Metal oxides as oxygen carriers and corresponding performances in the chemical looping partial oxidation process for hydrogen/syngas production are summarized. The regulation strategies for further improving reactivity and cycling stability are discussed. The ion diffusion and surface reactions are anatomized via theory calculations and characterizations. Abstract: The chemical looping partial oxidation (CLPO) process as a technology of chemical looping process (CLP) is recognized as a potential strategy for the efficient and clean conversion of fuels into syngas/H2 . Herein, in view of the importance of low-cost high-performance metal oxides as oxygen carriers (OCs) for this conversion, we systematically review the classification and CLPO applications of such OCs and discuss the improvement of OC reactivity and stability via the creation of metal–metal or metal–support synergism, the generation of oxygen vacancies, and the enhancement of deactivation resistance. Further, we present the results of theoretical and experimental characterizations probing ion diffusion and surface reactions to provide insights into the related reaction mechanisms and touch on the challenges and opportunities of developing metal oxides with excellent reactivity and long-term cycling stability in CLP. Thus, this review facilitates the design and performance regulation of OCs for future energy conversion systems.